Congenital heart block in fetuses of anti-SSA/SSB-positive mothers – treatment options, review 2021 - Opacian-Bojanowska, Monika; Murlewska, Julia; Kordjalik, Paulina; Strzelecka, Iwona (Prenatal Cardiology, 2022)
Immune-mediated complete heart block (CHB) is one of the most common reasons of fetal bradycardia, burdened with high morbidity, fetal mortality rate up to 19%. Even 70% of survivors require pacemaker implantation after birth or in early childhood. The recurrence rate of CHB in a subsequent pregnancy reaches 19%. Rare incidence of disease in population, limited experience, lack of standard treatment protocols are main issues. This article is a clue to therapeutic indications and options, based on literature review covering years: 2000-2020.